Ransomware Attack using AES Encryption on ECB, CBC and CFB Mode - Antariksa, Feillyan Alfreda (Jurnal Ilmu Komputer, 2019)
With the help of internet, users are faster getting data that they needed. It’s possible that villain insert an evil program (malware) without user knowing it. One of the malwares that spread like a plague right now is ransomware. The infected computer system will encrypt all files on the computer and blackmail the users to pay some money if you want to access back your files. For this experiment it’s using 2 approach, first is using online attack and second is offline attack. Ransomware in this experiment is using AES 256 for encrypting the files and using ECB, CBC and CFB mode for comparing time. As the result ECB is 39.5% faster than CBC and 7,17% faster than CFB. For CFB is 34,83% faster than CBC.